Edukasi Hukum Dan Hak-Hak Masyarakat di Lapas Cianjur - Wau, Anggriani; Sari, Putri Rena; Nasihin, Ahmad (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The absence of adequate understanding regarding prison laws can cause uncertainty and dissatisfaction in society.Purposes of Devotion: Provide an in-depth understanding to the public regarding the human rights of prisoners, legal procedures in prisons, and rehabilitation efforts carried out. Through this outreach, it is hoped that the community can better understand their role in supporting the reintegration of prisoners into society. Other goals are to reduce negative stigma towards prisoners, encourage community participation in rehabilitation programs, and stimulate positive attitude changes towards the criminal justice system. Thus, this outreach aims to create a supportive, fair environment and strengthen positive relations between the community and Cianjur Prison. Method of Devotion: First, using a visual presentation approach such as slides and supporting materials to provide a clear understanding of prison legal procedures and prisoners' rights. Next, a question and answer session was held to facilitate direct interaction between resource persons and participants, allowing for further clarification and discussion. Involving small discussion groups is also an effective method for stimulating the exchange of opinions and shared understanding. Finally, providing material in the form of brochures or pamphlets will make it easier for participants to understand and disseminate this information to the wider community. With this holistic approach, it is hoped that extension can achieve a positive and sustainable impact.Results of the Devotion: In accordance with the question and answer session and discussion, prisoners showed an interest in further exploring the human rights they have in prison, as well as how these rights can be exercised in everyday life. Findings also indicate that counseling creates an environment of open dialogue, allowing inmates to raise their questions and concerns regarding their rights and the legal process. With clearer information, prisoners feel more motivated to take part in the rehabilitation and resocialization programs offered by Cianjur Prison. Additionally, the findings highlighted that prisoners welcomed approaches that supported their rights, and as a result, saw improvements in self-confidence and psychological well-being among them. This indicates that legal education not only provides information, but also empowers prisoners to become more active in managing their rights and planning for the future after release.